Mechanical properties of vertical-inclined pile foundation for onshore wind turbines - Maogang Tian; Hechang Zhang; Shouhong Wang; Shilang Guo; Guangyuan Zhou; Shixin Ran; Bensheng Chen (PLoS ONE, 2025)
This study proposes an innovative Vertical-Inclined Pile Foundation to optimize the bearing performance of onshore wind turbine foundations. The Vertical-Inclined Pile Foundation (VIPF) and Vertical Pile Foundation (VPF) mechanical response mechanisms under wind turbine loading are compared based on the Hardening Soil (HS) model. Investigating the displacement distribution patterns, bearing platform deformations, pile internal force transfer, and pile-soil interaction laws of both foundation systems reveals the efficiency improvement mechanism of the VIPF. The results demonstrate that under identical loading conditions, the maximum displacement of the VIPF (20.63 mm) is 23.8% lower than that of the VPF (27.06 mm). The outer ring of inclined piles in the VIPF significantly enhances structural stiffness through spatial synergy, achieving uniform load distribution and effective redistribution of pile-body internal forces. Damage mode analysis indicates that the bearing platform primarily undergoes local tensile and compressive damage at the foundation ring-pile body connection, while the inclined piles establish an active pile-soil interaction system by strengthening soil confinement effects. Furthermore, parametric studies reveal that the pile base displacement exhibits a non-linear trend of initially decreasing and then increasing with larger inclination angles of the inclined piles. These findings provide a novel structural solution and theoretical basis for onshore wind turbine foundation engineering.